Bimbingan Teknis Peningkatan Pemahaman Penyusunan Laporan Keuangan terhadap Penerapan SAP pada Laporan Keuangan Pemerintah Kabupaten Kepulauan Meranti - Safrizal Safrizal; Nur Azlina; Wirdayani Wahab (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Financial reports as a form of obligation for an organization in the form of accountability, as is the case for local governments. The purpose of this community service activity is a form of contribution from the world of academia to the government in the form of technical guidance as an effort to increase understanding of the preparation of financial reports on the application of Government Accounting Standards (SAP) to the financial reports of the Meranti Islands District Government. The method of implementing this activity is through lectures accompanied by questions and answers, followed by exercises and practices related to the preparation of local government financial reports. The implementation of community service starts from the planning, preparation, implementation, and evaluation stages. Participants in this community service activity were attended by all government accounting staff of the Meranti Islands Regency and related officials. The results of this implementation show that the accounting staff of Kep.Meranti Regency have been able to prepare financial reports in accordance with applicable accounting standards. The implementation of this technical guidance is an important activity for every government, as an effort to increase the ability of accountants to prepare quality financial reports according to standards.